Sedimentation and regulation technologies in the Three Gorges Reservoir - Hu Chunhong; Fang Chunming (River, 2022)
Abstract Sedimentation is one of the key technical problems present throughout feasibility demonstration, design, construction, and operation of the Three Gorges Project. Since the Three Gorges Reservoir (TGR) began impoundment operation in 2003, important progress has been made in sedimentation and regulation technologies through systematic research and practices. This paper reveals the asynchronous propagation pattern of flood and sediment peak inflows, sediment movement in the backwater area during drawdown period, sediment flocculation, and sediment deposition that compromises the flood control reservoir storage, and puts forward new sediment regulation techniques, including sediment peak discharge regulation during flood season, siltation reduction in the backwater area during drawdown period, dynamic adjustment of the reservoir level during flood season, and joint sediment regulation in cascade reservoirs. A real‐time monitoring, forecasting and dynamic regulation platform for water and sediment inflow in the TGR was developed; a new mode of dynamic sediment regulation called “regulating sediment for greater benefits” is proposed, which addresses the constraints of sedimentation on the optimal operation of TGR. By enabling more flexible operation, this mode improves the process and pattern of sedimentation, ensures the safety of reservoir operation, and significantly augments the comprehensive benefits of the TGR.